CEOs' uncommon names and corporate innovation - Yuqi Gu (Cogent Economics & Finance, 2022)
I study the relationship between a Chief Executive Officer (CEO)'s uncommon name and corporate innovation. Consistent with the view that individuals with uncommon names prefer being distinctive, I document a significant positive relationship between CEO name uncommonness and corporate innovation quantity but not quality. To mitigate endogeneity concerns, I use the death of the CEO as a plausible exogenous shock and find results are robust in the difference-in-differences setting. I further show that the impact on innovation output is concentrated in the areas that are well-known to the company, of low economic value, and have a low scientific impact. Overall, the findings presented in this paper suggests that the heightened innovation activities by uncommonly named CEO exacerbate the investment distortions.
Keywords: G34; M12; O31; 330; CEO; corporate innovation; uncommon names